The influence of the video assistant referee on the Chinese Super League - Han, B.; Chen, Q.; Lago-Peñas, C.; Wang, C.; Liu, T. (International Journal of Sports Science & Coaching, 2020)
With the development and advancement of technology, various types of high-tech auxiliary equipment have been gradually introduced into football matches to assist referees to officiate the game. The Chinese football Super League (CSL) introduced the video assistant referee (VAR) in the 2018 season. The purpose of this study is to explore the impact of the introduction of VAR on football matches and on referees` performance. This study compared the data of all 240 games without VAR in the season 2017 and all 240 games with VAR in the season 2018 using Generalized Linear Model (GLM) and means comparison. The following match variables were considered: goals, penalties, red cards, yellow cards, fouls, offsides, playing time in the first half, playing time in the second half and total playing time. The study found that: 1) After the introduction of VAR, the number of offsides and fouls in the Chinese Super League dropped significantly (p < .001); 2) the playing time in the first and second half and the total playing time increased significantly(p < .001); 3) after the introduction of VAR, the home team advantage decreased slightly. The research result can help to better understand the impact of VAR on professional football, especially on the Chinese football Super League, it can also help referees to optimize their refereeing strategy.